2010
DOI: 10.1007/s11581-010-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of samarium hexaboride using tetra borate melt

Abstract: Fine crystals of samarium hexaboride were synthesized by molten salt electrolysis using samarium oxide, sodium tetraborate and lithium fluoride. The electrolysis was performed at 900°C in argon atmosphere at various current densities ranging from 1.0 to 2.3 A/cm 2 . The molar ratio of the reactants [Sm:B] was varied from 1:6 to 1:12. The deposited crystals were examined for the phase purity using X-ray diffraction analysis. The effect of current density and the influence of molar concentration of the reactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Jose et al reported the “unstable stoichiometric way” for the deposition of Barium hexaboride [ 14 ]. We reported earlier that the electrolytically dissociated metal and B ions deposit on the cathode as CeB 6 and SmB 6 , respectively [ 15 , 16 ]. We also reported in our earlier study on CaB 6 that the calcium and boron are reduced at the cathode to form submicron sized crystals [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jose et al reported the “unstable stoichiometric way” for the deposition of Barium hexaboride [ 14 ]. We reported earlier that the electrolytically dissociated metal and B ions deposit on the cathode as CeB 6 and SmB 6 , respectively [ 15 , 16 ]. We also reported in our earlier study on CaB 6 that the calcium and boron are reduced at the cathode to form submicron sized crystals [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The base pressure of the measurement chamber is lower than 5 × 10 −5  Pa, and the distance between cathode and anode ranges from 100 to 500 μm except individual Si nano-apex (100 nm). UPS (Thermo Fisher Scientific, ESCALAB 250) and Kelvin probe force microscopy (KPFM, Omicron VT-AFM) techniques were respectively used to measure the work function of ZnO 37 , CuO 38 and B 39 nanowires while other one-dimensional nanomaterials adopted the work function of their corresponding bulk counterparts 24,35,3941 . Their electric conductivity was also obtained by our modified in-situ microprobe measurement technique.…”
Section: Methodsmentioning
confidence: 99%
“…Various processes have been reported for the preparation of SmB 6 powders. Several groups have reported SmB 6 synthesis by reaction of metal (eg, Sm, Sm 2 O 3 , or SmCl 3 ) and boron sources (eg, B, B 4 C, B 2 O 3 , B/C mixture, NaBH 4 , or Na 2 B 4 O 7 ) . SmB 6 particles were synthesized at 1500‐1800°C by borothermal or boro/carbothermal reductions (BCTR) of Sm 2 O 3 with B, B 4 C, or a B/C mixture under vacuum or H 2 .…”
Section: Introductionmentioning
confidence: 99%